Conséquences de la téléphonie mobile de cinquième génération sur la télé-géographie - Edward M. Roche; Benjamin H. Dickens-Jr.; Walker Townes (Netcom)
The “5G” new generation of wireless telecommunications technology promises to revolutionize how the world communicates. It he makes obsolete many traditional methodologies employed in tele-geography studies, but at the same time we can expect to ﬁnd new vectors of both theoretical and applied research.